EP 147. Electrophysiological evaluation of uremic patients undergoing hemodialisys: Proposal of a clinical and numerical scale for severity and prognosis. Issue 9 (September 2016) - Pereira, V.C.; Resende, L.A.D.; Ponce, D.; Balbi, A.; Barretti, P.
Abstract : Introduction: Conduction studies (ENMG) have been used since long time for evaluation of chronic uremia (O'Regan et al., 2012 ) and the blink reflex is important for this purpose. Neurological alterations are easy to detect in uremic patients (Vellanki and Bansal, 2015 ), such as deep hyperreflexia, asterixis, reading and memory disturbances and sleep disorders (Merlino et al., 2008 ). They can occur together or alone in early stages of chronic uremia, but they have not been quantified to this moment, the purpose of this study. Methods: Peripheral neuropathy was diagnosed by ENMG and classified into four levels: Normal – 0.0 point; mild – 1, 0 point; moderate – 2, 0 points; marked – 3, 0 points. The blink reflex was classified into Normal – 0.0 point; R1 alterations – 1, 0 point; one side R2 alteration – 2, 0 points; both sides R2 alterations – 3, 0 points. Maximal electrophysiological assessment: 6, 0 points. Clinical alterations were defined as having or not asterixis (0.0 or 1, 0 point, respectively), having or not deep hyperreflexia (0.0 or 1, 0 point); having or not reading and/or memory disorders (0.0 or 1.0), having or not sleep disorders (0.0 or 1.0). Clinical evaluation: maximum of 4, 0 points. The full scale ranges from zero to ten (10) points in ascending graduation related to the severity (Table 1 ). Results: In previous studies of 30 patients in our Service were documented several alterations of the blink reflex, some of them with prognostic value. Attenuated R2 responses occurred in patients who died soon after the study. The application of the proposed scale for the first 10 patients showed results between 1 to 7 points. Values of 1 to 3 were observed in patients with shorter time of dialysis treatment and 6 or 7 values in patients with longer time of dialysis. Conclusions: This study propose a new scale of assessment of the central and peripheric nervous system impairment in chronic uremia. The procedures are non-invasive, fast, easy to apply and already showed to be useful. They can be applied by nephrologists and neurologists, to teaching and research in interdisciplinarity Neurology/Nephrology.